Pendidikan Kesehatan Pencegahan Penyakit Akibat Kerja Sebagai Upaya Peningkatan Produktivitas Kerja - Dhonna Anggreni; Henry Sudiyanto; Eka Diah Kartiningrum; Sulis Diana; Muhammad Yusuf Alamudi; Arief Fardiansyah (Jurnal Pengabdian Masyarakat, 2026)
Improving the quality of human resources is an effort to increase intelligence and work productivity. One effort made to improve the quality of human resources is by improving the health of the public in general and specifically workers. This community service activity aims to increase the knowledge of factory workers regarding steps to prevent occupational diseases so that they do not contract or transmit diseases to their colleagues. This activity was carried out at PT. X in Mojokerto City with the target of the activity being 40 factory workers. This activity consisted of several stages, namely the preparation stage, implementation, and evaluation. In the implementation stage, the activity was carried out through providing health education and health checks. From the evaluation results, it was found that the knowledge of PT. X workers increased after being provided with health education and the results of the health checks were also quite good. The results of the health checks are expected to be a reference for the factory to determine steps to control the risk of health problems among workers.